Accumulation of manganese oxides in biological activated carbon filters: Implications for biodegradation studies. Issue 4 (29th August 2022) - Bernstein, Daniel R.; Glasgow, Graeme D. E.; Lay, Mark C.; Manley‐Harris, Merilyn
Abstract: A comparison of granular and biological activated carbon (GAC and BAC) media used for drinking water treatment was made to assess differences in surface elemental composition. Fresh GAC, recently commissioned GAC and end‐of‐service life BAC from a water treatment plant in New Zealand were analyzed using scanning electron microscopy, energy‐dispersive spectroscopy, and inductively coupled plasma‐mass spectrometry (ICP‐MS). Imaging revealed dense microbial colonization of the BAC surface compared to GAC media, and a mineralized surface layer high in manganese and oxygen. ICP‐MS analysis also confirmed high levels of Mn in the BAC media relative to GAC media. As many bacterial species known to colonize BAC filters are also known as Mn oxidizers, this suggests a biogenic origin of the Mn‐oxide deposition on the BAC surface. Given the properties of Mn‐oxides, they may be implicated in the mechanism by which bacteria capture and metabolize substrates in BAC filters.